(untitled) (Journal of Comparative & International Higher Education, 2021)
In recent years, international and national university ranking exercises have become commonplace, serving a host of stakeholders and beneficiaries including students, institutions, and governments. As such, they have drawn increasing scrutiny from academics and other observers, many of whom have called into question the integrity of the methodologies employed, and thus the outcomes of the process. By contrast, relatively little attention has been paid to largely external factors that can affect a given institution’s ability to compete within a given ranking exercise, such as their corporate status, geographic location, and/or access to resources. Building on previous work examining the impact of such “extraneous” factors, this study undertakes a quantitative analysis of the best-known university ranking exercise in Brazil to better understand the impact of such variables, both within other national contexts and well beyond.